The Weekly Pattern in Stock Returns: Cash versus Futures: A Note - Cornell, Bradford (Journal of Finance, 1985)
This paper presents tests designed to determine whether the weekly pattern in stock returns continues after the introduction of futures trading on stock indexes and whether the pattern carries over to the futures market. Using data for the SP500, I find that the “Monday effect” does persist in the cash market, but there is no evidence of a similar pattern in the futures market.